2020
DOI: 10.3390/polym12061382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical Modifications on the Thermoresponsive Behavior of a PDMAEA-b-PNIPAM-b-POEGA Triblock Terpolymer

Abstract: In this work, the synthesis, selective chemical modifications, and self-assembly behavior in aqueous media of a novel poly(2-(dimethylamino)ethyl acrylate)20-b-poly(N-isopropylacrylamide)11-b-poly(oligo ethylene glycol methyl ether acrylate)18 (PDMAEA20-b-PNIPAM11-b-POEGA18) dual-responsive (pH and temperature) and triply hydrophilic amino-based triblock terpolymer are reported. The amine functional triblock terpolymer was synthesized by sequential reversible addition fragmentation chain transfer polymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Other amphiphilic and thermoresponsive triblock bipolymers have been investigated as thermoresponsive gels. These include polymers based on poly­(ethylene glycol) (PEG) which consist of a block with an ester-based backbone, (meth)­acrylate and acrylamide polymers, such as polymers based on N -isopropylacrylamide (NIPAAm), ,, PEG (meth)­acrylate units, and 2-(dimethylamino)­ethyl methacrylate (DMAEMA), and poly­(oxazoline)­s. Amphiphilic triblock terpolymers have also been investigated, and the position of the block has been proven critical for the final application. , Interestingly, when triblock bi- or terpolymers were compared to their diblock counterparts, it was concluded that triblock copolymers form stronger gels at lower temperatures and concentrations. , Therefore, increasing the number of blocks and/or comonomers seems to favor gelation. Due to their unique reversible thermogelling properties, thermoresponsive gels have become popular candidates in tissue engineering, , drug delivery, , and three-dimensional (3-D) printing , fields.…”
Section: Introductionmentioning
confidence: 99%
“…Other amphiphilic and thermoresponsive triblock bipolymers have been investigated as thermoresponsive gels. These include polymers based on poly­(ethylene glycol) (PEG) which consist of a block with an ester-based backbone, (meth)­acrylate and acrylamide polymers, such as polymers based on N -isopropylacrylamide (NIPAAm), ,, PEG (meth)­acrylate units, and 2-(dimethylamino)­ethyl methacrylate (DMAEMA), and poly­(oxazoline)­s. Amphiphilic triblock terpolymers have also been investigated, and the position of the block has been proven critical for the final application. , Interestingly, when triblock bi- or terpolymers were compared to their diblock counterparts, it was concluded that triblock copolymers form stronger gels at lower temperatures and concentrations. , Therefore, increasing the number of blocks and/or comonomers seems to favor gelation. Due to their unique reversible thermogelling properties, thermoresponsive gels have become popular candidates in tissue engineering, , drug delivery, , and three-dimensional (3-D) printing , fields.…”
Section: Introductionmentioning
confidence: 99%
“…Giaouzi et al [ 57 ] worked on the synthesis and self-assembly in H 2 O of poly(2-(dimethylamino)ethyl acrylate)- b -poly( N -isopropylacrylamide)- b -poly(oligo ethylene glycol methyl ether acrylate), (PDMAEA- b -PNIPAM- b -POEGA) triple hydrophilic and double-responsive (temperature and pH) triblock terpolymers. The synthesis was achieved by three-step RAFT polymerization in dioxane, involving 2-(dodecylthiocarbonothioylthio)-2-methylpropionionic acid as the CTA.…”
Section: Abc-type Linear Triblock Terpolymersmentioning
confidence: 99%
“…Some of the latest reports are based on linear di‐ and triblocks where one block is the well‐studied poly( N ‐isopropylacrylamide) to confer the thermoresponsivity and other blocks often contain a weak acid or base such as (meth)acrylic acid and 2,2 dimethyl ethyl (meth)acrylate (DMAEMA). Some examples are: PDMAEMA‐ b ‐PNIPAm‐ b ‐POEGA, [ 167 ] PDMAEMA‐ b ‐PNIPAm where the 2 blocks are connected via a host–guest interaction based on pillar[5]arene and viologen ( Figure ), [ 168 ] PAA‐ b ‐PNIPAm, [ 169 ] PMAA‐ b ‐PNIPAm, [ 170 ] and PNIPAm‐ b ‐PDOPA where the PNIPAm chain ends are modified with a 3,4‐dihydroxy‐ l ‐phenylalanine moieties forming spherical nanoparticles with temperature/pH dual‐stimuli‐responsive character. [ 171 ] Other examples including PNIPAM‐ b ‐P(DPA‐ co ‐TPE) and P(NIPAM‐ co ‐TPE)‐ b ‐PDPA where tetraphenylethylene (TPE) is used as a single‐color “turn on” fluorescence probe used to differentiate temperature or pH stimulus in solutions or in the cells.…”
Section: Novel (Co)polymers By Raft and Their Propertiesmentioning
confidence: 99%